Food intake patterns and associations with postpartum weight retention in women living with and without HIV in Cape Town South Africa - Sithole, Siphesihle (Department of Public Health and Family Medicine, 2025)
Background: Maternal nutrition during pregnancy and postpartum may significantly impacts weight outcomes and long-term maternal health. However, dietary habits and weight outcomes during these periods remains poorly understood particularly in obesogenic environments like Gugulethu township (Cape Town, South Africa). In addition, dietary habits among persons living HIV may differ from the general public due to increased nutritional demands. However, there is limited data on food intake and weight outcomes in low-income resource settings. Therefore, the aim of this study was to investigate food intake patterns during pregnancy and postpartum, and associations with gestational weight gain (GWG) and postpartum weight retention (PPWR) among women living with and without HIV. Methods: This Master of Public Health mini-dissertation presents a research protocol (section A) and a journal-formatted manuscript (Section C). This study was a retrospective secondary data analysis study which builds on the Cardiometabolic Risk in Pregnancy (CAMP) a prospective cohort study of 400 pregnant women (n = 200 living with HIV and n = 200 living without HIV) recruited and enrolled from November 2019 to October 2022. Food intake was assessed using the Minimum Dietary Diversity for Women (MDD-W). Food intake was stratified using HIV, GWG and PPWR respectively. Weight assessments in pregnancy and postpartum periods were conducted by a trained study nurse and GWG was categorised as adequate, inadequate, and excessive weight gain according to the Institute of Medicine (IOM) guidelines and PPWR was categorised as weight loss (<0kg), normal weight retention (0-5kg) and excessive weight retention (>5kg). Multinomial regression models examined associations between food intake, GWG and PPWR while controlling for confounders including parity, income marital status as well education level. Results: Overall, 82% of women were multigravida while the overall median age was 30.1 (IQR, 25.4- 34.0). Women living with HIV exhibited higher food intake and dietary diversity during gestation, with significant differences in the consumption of starchy staples (38%) and meats (37%) compared to women without HIV (26% for both). Women living with HIV compared to those living without HIV were more likely to experience inadequate weight gain as opposed to adequate weight gain (OR = 2.24 95% CI 1.12, 4.46). Postpartum, excessive weight retention was associated with milk and milk product consumption, where women consuming milk and milk products compared to those not consuming milk and milk products, were more likely to experience excessive weight retention relative to those who experienced normal weight retention (OR = 2.278 95% CI, 1.10,7.05) while holding all other covariates constant. Conclusion: Our results add valuable insights to the current knowledge by offering detailed perspectives on the complex connections between dietary diversity and its broader consequences on maternal aspects such as GWG and PPWR. Targeted nutritional interventions are needed to promote healthy weight during pregnancy and postpartum periods, particularly among women living with HIV.